(untitled) (Coffee Science - ISSN 1984-3909, 2011)
The signals that regulate the induction and differentiation of floral buds in coffee are still not fully known, but are promoted by biochemical and physiological factors related to the photoperiod, light intensity, water, temperature and C/N ratio. The study of morphological characters in different floral development stages of the Coffea arabica L. cultivars is relevant to assessing the sensitivity of coffee to environmental factors due to differences observed between cultivars. The aim of this work was to study the morphological differentiation of buds in adult cultivars of the coffee trees; Catuaí Obatã and Tupi, grown under ambient conditions of Campinas, Brazil, in relation to fruit production and other physiological characteristics. Slides of Longitudinal-axial sections were mounted for the characterization and quantification of the histological stages of bud differentiation. Phenological development was evaluated by measuring the growth of flowers and fruits and water potential. The differentiation of reproductive buds occurred at the same time in the Obatã and Tupi cultivars and in a distinct phase in Catuaí, as seen in 2005 where it first occurred in Catuaí ‘and later in’ Obatã ‘and’ Tupi ‘and in reverse order the next year. Over the two years of study, the first stage (bud undifferentiated) remained until mid-March in all cultivars studied and in greater percentage. From April until mid-June, the first stage declined, with a predominance of stage 2 (broadened buds) and 3 (differentiated buds). After this period, stages 2 and 3 predominated until early September, a period when floral buds were green and latent, characteristic of stage 4.